Effects of Pregnancy Anesthesia on Fetal Nervous System - Li, Xingyue; Jiang, Xi; Zhao, Ping (Frontiers in Pharmacology, 2021)
The effects of general anesthesia on the developing brain remain a great concern in the medical field and even in the public, and most researches in this area focus on infancy and childhood. In recent years, with the continuous development of medical technology, the number of operations during pregnancy is increasing, however, studies on general anesthesia during pregnancy are relatively lacking. The mid-trimester of pregnancy is a critical period, and is regarded as a safe period for surgery, but it is a fragile period for the development of the central nervous system and is particularly sensitive to the impact of the environment. Our research group found that general anesthesia may have adverse effects on fetal neurodevelopment during the mid-trimester. Therefore, in this review, we summarize the characteristics of anesthesia during pregnancy, and the related research of the anesthesia’s impacts on the development of central nervous system were introduced.